Novel corona virus (COVID-19); Global efforts and effective investigational medicines: A review - Madhusudan Goyal; Nisha Tewatia; Hemlata Vashisht; Reena Jain; Sudershan Kumar (Elsevier, 2021)
Coronavirus disease-2019 (COVID-19), associated with the outbreak of deadly virus originating in Wuhan, China, is now a global health emergency and a matter of serious concern. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is rapidly spreading worldwide, and WHO declared the outbreak of this disease a pandemic on March 11, 2020. Though some of the countries have succeeded in slowing down the rate of the spread of this pandemic, most the countries across the globe are still continuing to experience an increasing trend in the growth and spread of this deadly disease. Hence, in the current scenario, is has now become essential to control and finally irradicate this deadly disease using an effective vaccine. One can expect the prominent role of already available antivirals, antibodies and anti-inflammatory drugs in the market, in this pandemic. Immunomodulatory and biological therapeutics are also in the high expectations to combat COVID-19. RNA based vaccines might be more advantageous over traditional vaccines, to deal with the pandemic threat. Aiming towards this direction, clinical trials for SARS-CoV-2 vaccine are currently underway all across the globe. Currently, about 150 health related organizations and research labs are in the progress for the evolution of COVID-19 vaccines, globally. The initial aim of these clinical trials is to assess vaccine's safety, which is tested in Phase I/II/III studies where the primary outcomes typically examine the frequency of adverse effects. The vaccine is about to undergo phase III testing in several countries such as India, USA, South Africa, Brazil and England. US Government, under Operation Wrap Speed is even ready to sponsor three candidates, namely-The University of Oxford and AstraZeneca's AZD1222; Moderna's mRNA-1273; and Pfizer and BioNTech's BNT162 for Phase III trials.